Analysing architecture. - Unwin, Simon, ....- (Londen : Routledge, 2009)
Clear and accessible, Analysing Architecture opens a fresh way to understanding architecture. It offers a unique 'notebook' of architectural strategies to present an engaging introduction to elements and concepts in architectural design. Beautifully illustrated throughout with the author's original...
Inhoudsopgave : How Analysis Helps Design Architecture as Identification of Place Basic Elements of Architecture Modifying Elements of Architecture Elements Doing More Than One Thing Using Things That Are There Primitive Place Types Architecture as Making Frames Temples and Cottages Geometries of Being Ideal Geometry Themes in Spatial Organisation Postscript Case Studies
Keywords: Architectuur; Gebouwen; Ontwerpen